Renewable energy, economic growth, and CO2 emissions contained Co-movement in African oil-producing countries: A wavelet based analysis - Olivier Joseph Abban; Yao Hongxing; Alina Cristina Nuta; Alex Boadi Dankyi; Charles Ofori; Joana Cobbinah (Energy Strategy Reviews, 2022)
Electricity power generation has gradually expanded in Africa, especially in oil-producing countries. Although natural gas and coal produced most of the electricity, renewable energy sources (REW) played a significant role in total electricity generation, with hydro being the most prevalent. This study examined the nexus between renewable energy, CO2 emissions, and economic growth in terms of time, space, and the combined time-frequency sphere using wavelet analysis. The following are the primary research questions: (a) Do the employed variables under examination have a long-term relationship? (b) What is the strength of the nexus between renewable energy, economic growth, and CO2 emissions at different time and frequency frames? (c) Do the independent variables have an anti-cyclic association with CO2 emissions? The empirical results confirmed that: (a) there is evidence of a short-run association among the variables at different frequency scales. (b) The wavelet coherence results provide evidence of a strong association among the variables in the long-run estimation, which is supported by the Trace analysis and the Toda-Yamamoto causality. (c) The findings revealed that REW and CO2 are out of phase and have an anti-cyclic impact, with REW driving the cycle. Accordingly, appropriate policy measures are advocated to ensure that these African economies under study are on a path to sustainability.